Electrochemical corrosion detection method for square aluminum shell lithium ion battery
Patent Information
- Application Number
- CN202611090589.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-09
AI Technical Summary
此时,铝壳与正极之间会形成原电池,引发电化学腐蚀,最终导致电池漏液而报废
1.通过采用Ag/AgCl双盐桥参比电极,消除了正极嵌锂量差异导致的电位波动;通过采用配制的0.1~0.5mol/L K2SO4水溶液作为检测电解液,避免了电池内部电解液浓度波动对检测结果的干扰;通过将电池正负极保持开路状态并浸润于电解液中,消除了铝壳与负极之间的接触阻抗影响;通过采集参比电极与铝壳之间的原电池电压并与预设阈值比较,实现了对铝壳腐蚀风险的精准检测,有效解决了现有技术误判和漏判的问题,提高了检测的准确性、稳定性和可靠性;
Smart Images

Figure CN122882552A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of production and testing technology for square aluminum-cased lithium-ion batteries, specifically to an electrochemical corrosion detection method for square aluminum-cased lithium-ion batteries. Background Technology
[0002] During the production of square aluminum-cased lithium-ion batteries, fluctuations in the manufacturing process can lead to abnormal conductivity between the negative electrode and the aluminum casing. In this case, a galvanic cell forms between the aluminum casing and the positive electrode, causing electrochemical corrosion and ultimately resulting in battery leakage and scrap. Currently, the common technique used on production lines is to measure the voltage across the positive electrode and the aluminum casing to screen for defective products with corrosion risks.
[0003] However, this existing technology has significant shortcomings. First, the lithium intercalation amount of the positive electrode varies due to the influence of charge and discharge accuracy, and the electrolyte concentration also varies due to process fluctuations such as coating, electrolyte injection, and side reactions. These factors can cause changes in the positive electrode potential of different batteries, resulting in a large distribution range of edge voltage test values, which can easily lead to misjudgments. Second, when a micro-short circuit exists between the aluminum casing and the negative electrode, the measured edge voltage data is scattered, which can easily lead to missed detections, allowing defective products to enter subsequent processes. Therefore, the accuracy, stability, and reliability of existing edge voltage detection methods are insufficient to meet the battery quality control requirements of production lines.
[0004] Therefore, this application studies an electrochemical corrosion detection method for square aluminum-cased lithium-ion batteries, which can improve the accuracy, stability and reliability of the detection. Summary of the Invention
[0005] In order to improve the accuracy, stability and reliability of detection, this application provides an electrochemical corrosion detection method for square aluminum-cased lithium-ion batteries.
[0006] This application provides an electrochemical corrosion detection method for square aluminum-cased lithium-ion batteries, employing the following technical solution: An electrochemical corrosion detection method for square aluminum-cased lithium-ion batteries includes the following steps: Step S1: After completing the K-value test on the production line, keep both the positive and negative electrodes of the square aluminum-cased lithium-ion battery in an open circuit state and use it as the battery to be tested. Step S2: Construct the detection electrochemical system, using an Ag / AgCl dual salt bridge reference electrode as the reference electrode and the aluminum metal shell of the battery under test as the working electrode. Prepare a K2SO4 aqueous solution with a concentration of 0.1~0.5mol / L as the detection electrolyte; wherein, the inner salt bridge of the Ag / AgCl dual salt bridge reference electrode is filled with saturated KCl solution, and the outer salt bridge is filled with K2SO4 solution of the same system as the detection electrolyte; Step S3: Place the battery under test in the open circuit state into the detection tank containing the K2SO4 aqueous solution, and let it stand for 3 to 5 seconds to allow the potential between the battery aluminum shell and the electrolyte to stabilize. Step S4: Attach the test probe to the outer wall of the aluminum shell of the battery under test, so that the Ag / AgCl dual salt bridge reference electrode, K2SO4 detection electrolyte, and battery aluminum shell form a closed galvanic cell circuit, and collect the measured voltage value V of the galvanic cell at an environment of 25±3℃. Step S5: Compare the measured voltage value V with the preset corrosion judgment threshold. If the voltage V is greater than the corrosion judgment threshold, the aluminum shell of the battery is determined to have an electrochemical corrosion leakage risk and is marked as a defective product; otherwise, it is determined to be a qualified product.
[0007] By adopting the above technical solution, the potential fluctuations caused by differences in the amount of lithium intercalated in the positive electrode are eliminated by using an Ag / AgCl dual salt bridge reference electrode; the interference of electrolyte concentration fluctuations inside the battery on the detection results is avoided by using a prepared 0.1~0.5mol / L K2SO4 aqueous solution as the detection electrolyte; the influence of contact impedance between the aluminum shell and the negative electrode is eliminated by keeping the positive and negative electrodes of the battery in an open circuit state and immersing them in the electrolyte; and the accurate detection of aluminum shell corrosion risk is achieved by collecting the galvanic voltage between the reference electrode and the aluminum shell and comparing it with a preset threshold, effectively solving the problems of misjudgment and missed judgment in the existing technology, and improving the accuracy, stability and reliability of the detection.
[0008] Optionally, the corrosion judgment threshold in step S5 is 0.500V; when the measured voltage value V > 0.500V, it is judged as a defective product, and when V ≤ 0.500V, it is judged as a qualified product.
[0009] By adopting the above technical solution, the corrosion judgment threshold is specifically limited to 0.500V, which is based on the corrosion potential of the aluminum shell (0.23V vs Li / Li). + ) and Ag / AgCl reference electrode potential (3.237V vs Li / Li + The theoretical difference is 3.007V. Considering the micro-short circuit between the negative electrode and the shell and the influence of environmental factors, the corrosion boundary voltage is set at 0.500V. This gives the judgment standard a clear theoretical basis and engineering margin, avoids the risk of misjudgment caused by empirical thresholds, and further improves the accuracy of detection.
[0010] Optionally, between step S4 and step S5, step S41 is also included: online real-time detection of the conductivity and solution temperature of the detection electrolyte, error compensation correction of the measured voltage value V collected in step S4 based on the liquid junction potential and ambient temperature deviation, to obtain the corrected voltage value V', and the corrected voltage value V' is used to replace the measured voltage value V for threshold determination in step S5.
[0011] By adopting the above technical solution, an error compensation and correction step is added between voltage acquisition and threshold determination. The conductivity and temperature of the electrolyte are detected online in real time, and the measured voltage value is corrected based on the liquid junction potential and the deviation of ambient temperature. This eliminates the influence of electrolyte concentration fluctuations and ambient temperature changes on the measurement results, further improves the accuracy and stability of the detection, and effectively solves the misjudgment problem caused by differences in electrolyte concentration and ambient temperature fluctuations in the existing technology.
[0012] Optionally, an integrated conductivity and temperature sensor can be used to synchronously collect the concentration and temperature parameters of the detection electrolyte online.
[0013] By adopting the above technical solution and using an integrated conductivity temperature sensor to simultaneously collect the concentration and temperature parameters of the electrolyte, integrated and real-time monitoring of two key influencing factors is achieved. This simplifies the structure of the detection system, avoids the problem of data asynchrony caused by time-sharing or device-sharing acquisition, provides accurate and synchronous input parameters for error compensation and correction, and ensures the effectiveness of the correction effect.
[0014] Optionally, the test probe is made of gold-plated copper to make low-impedance contact with the outer wall of the battery's aluminum casing.
[0015] By adopting the above technical solution and using a test probe made of gold-plated copper, the excellent conductivity and oxidation resistance of gold material are utilized to achieve low impedance and high stability contact between the probe and the aluminum shell of the battery. This avoids the problem of low voltage measurement value caused by poor contact and effectively solves the problem of missed judgment caused by high contact impedance in the existing technology.
[0016] Optionally, before step S1, step S01 is also included: routine calibration and electrolyte maintenance. Step S01 specifically includes: monthly potential calibration of the Ag / AgCl dual salt bridge reference electrode using an electrochemical workstation, with the calibration deviation controlled within 3mV. If the deviation exceeds the limit, the reference electrode is replaced; the conductivity of the detection electrolyte is monitored in real time, and when the fluctuation exceeds ±0.72mS / cm, the K2SO4 detection electrolyte is prepared and replaced.
[0017] By adopting the above technical solution, and by setting up routine calibration and electrolyte maintenance steps before the detection step, the reference electrode is regularly calibrated for potential and the calibration deviation is strictly controlled. At the same time, the electrolyte conductivity is monitored in real time and unqualified electrolyte is replaced in time. This ensures that the reference electrode and electrolyte used for detection are in standard condition for a long time, avoids detection errors caused by electrode aging or electrolyte deterioration, and ensures the long-term stability and repeatability of the detection method.
[0018] Optionally, the industrial screening reference voltage is 3.007V, and the internal control judgment threshold is 0.500V.
[0019] By adopting the above technical solution, and setting an industrial screening reference voltage of 3.007V and an internal control judgment threshold of 0.500V, where 3.007V is the theoretical corrosion threshold based on electrochemical principles and 0.500V is the tightening threshold after considering the influence of liquid junction potential and temperature, a two-level judgment system of theoretical reference and internal control tightening is formed. This ensures the scientific basis of screening and reserves a safety margin for fluctuations in the production line environment, effectively balancing the sensitivity and false judgment rate of detection.
[0020] Optionally, after step S5, step S6 is also included: cleaning step: remove the battery from the test electrolyte tank and clean the residual aqueous solution on the surface of the battery casing by using a combination of air blowing and roller wiping.
[0021] By adopting the above technical solution, and adding a cleaning step after testing, the residual K2SO4 aqueous solution on the battery casing surface is effectively removed by using a combination of air blowing and roller wiping. This avoids the risk of contamination or corrosion from electrolyte residue to subsequent battery processes (such as electrolyte injection, formation, and capacity testing), ensuring that the testing method does not introduce new quality problems in production line applications and has good process compatibility. In summary, this application includes the following beneficial technical effects: 1. By employing an Ag / AgCl dual-salt bridge reference electrode, potential fluctuations caused by differences in lithium intercalation at the positive electrode are eliminated; by using a prepared 0.1~0.5mol / L K2SO4 aqueous solution as the detection electrolyte, interference from fluctuations in the internal electrolyte concentration of the battery on the detection results is avoided; by keeping the positive and negative electrodes of the battery in an open-circuit state and immersing them in the electrolyte, the influence of contact impedance between the aluminum shell and the negative electrode is eliminated; by collecting the galvanic voltage between the reference electrode and the aluminum shell and comparing it with a preset threshold, accurate detection of aluminum shell corrosion risk is achieved, effectively solving the problems of misjudgment and missed judgment in existing technologies, and improving the accuracy, stability and reliability of detection; 2. The corrosion threshold is specifically defined as 0.500V, based on the corrosion potential of the aluminum casing (0.23V vs Li / Li). +) and Ag / AgCl reference electrode potential (3.237V vs Li / Li + The theoretical difference is 3.007V, and after further consideration of the liquid junction potential and the deviation of the ambient temperature, it is tightened to obtain the judgment standard, which has a clear theoretical basis and engineering margin, avoids the risk of misjudgment caused by empirical thresholds, and further improves the accuracy of detection. 3. By adding an error compensation correction step between voltage acquisition and threshold determination, the conductivity and temperature of the electrolyte are detected online in real time. The measured voltage value is corrected based on the liquid junction potential and the deviation of ambient temperature, eliminating the influence of electrolyte concentration fluctuations and ambient temperature changes on the measurement results. This further improves the accuracy and stability of the detection and effectively solves the misjudgment problem caused by differences in electrolyte concentration and ambient temperature fluctuations in the existing technology. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other embodiments can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a schematic diagram of the electrochemical corrosion detection method for a square aluminum-cased lithium-ion battery according to an embodiment of this application; Figure 2 These are the voltage test results of the control group in this application; Figure 3 This is the voltage test result of the electrochemical corrosion detection method for the square aluminum-cased lithium-ion battery according to the embodiments of this application; Figure 4 The results are the temperature-voltage correlation test results of the electrochemical corrosion detection method for square aluminum-cased lithium-ion batteries according to embodiments of this application.
[0024] Reference numerals in the attached diagram: 1. Detection cell; 2. Battery under test; 3. Reference electrode; 31. Inner salt bridge; 32. Outer salt bridge; 4. Conductivity-integrated temperature sensor; 5. Probe; 6. Voltmeter. Detailed Implementation
[0025] The following is in conjunction with the appendix Figure 1-4 This application will be described in further detail.
[0026] This application discloses an electrochemical corrosion detection method for square aluminum-cased lithium-ion batteries.
[0027] Example 1: Reference Figure 1The electrochemical corrosion detection method for square aluminum-cased lithium-ion batteries includes the following steps: Before step S1, there is also step S01: routine calibration and electrolyte maintenance. Step S01 specifically includes: monthly potential calibration of the Ag / AgCl dual salt bridge reference electrode using an electrochemical workstation, with the calomel electrode as the standard, and the calibration deviation controlled within 3mV. If the deviation exceeds the standard, the reference electrode is replaced. According to the test, the deviation of the reference electrode used in this embodiment is +0.2mV, which meets the requirements.
[0028] The conductivity of the detection electrolyte was monitored in real time, with a standard conductivity value set at 36 mS / cm (corresponding to a concentration of 0.3 mol / L). When the fluctuation exceeded ±0.72 mS / cm, the K2SO4 detection electrolyte was prepared and replaced. The current electrolyte conductivity was measured to be 36.2 mS / cm, which meets the requirements.
[0029] Step S1: After completing the K-value test on the production line, keep the positive and negative electrodes of the square aluminum-cased lithium-ion battery in an open circuit state as the battery to be tested; the model of the square aluminum-cased lithium-ion battery is NCM 2614891-51Ah, the nominal capacity is 51Ah, the length is 148mm, the thickness is 26mm, and the height is 91mm.
[0030] Step S2: Construct the detection electrochemical system. An Ag / AgCl dual-salt bridge reference electrode is fixed in the detection cell as the reference electrode, and the aluminum metal casing of the battery under test is used as the working electrode, forming the detection electrochemical system with the reference electrode. A K₂SO₄ aqueous solution with a concentration of 0.1~0.5 mol / L is prepared as the detection electrolyte. In this embodiment, the Ag / AgCl dual-salt bridge reference electrode is completely immersed in the 0.3 mol / L K₂SO₄ detection electrolyte. The inner salt bridge of the Ag / AgCl dual-salt bridge reference electrode is filled with a saturated KCl solution, and the outer salt bridge is filled with a K₂SO₄ solution of the same system as the detection electrolyte. The inner and outer salt bridges are separated by porous ceramic to prevent Cl₂ from forming. - Ions migrate into the detection electrolyte and cause corrosion to the aluminum shell.
[0031] Step S3: Place the battery under test in the open circuit state into the test tank containing the K2SO4 aqueous solution, so that the aluminum shell of the battery is completely submerged below the surface of the electrolyte, and let it stand for 3 to 5 seconds to allow the potential between the aluminum shell of the battery and the electrolyte to stabilize. Step S4: The test probe is attached to the outer wall of the aluminum casing of the battery under test. The test probe is made of gold-plated copper and makes low-impedance contact with the outer wall of the aluminum casing. The test probe is tightly attached to the outer wall of the aluminum casing of the battery under test. The Ag / AgCl dual salt bridge reference electrode, K2SO4 electrolyte detection, and battery aluminum casing form a closed galvanic cell circuit. The measured voltage value V of the galvanic cell is collected at 25±3℃. A HIOKI DM7275 high-precision voltmeter is used to collect the measured voltage value V of the galvanic cell. Three consecutive measurements are taken, and the average value is taken as the measured voltage value of the battery. In this embodiment, the measured voltage value V of a certain battery is 0.403V.
[0032] Between steps S4 and S5, step S41 is also included: online real-time detection of the conductivity and solution temperature of the detection electrolyte. Simultaneously with voltage acquisition, the conductivity and solution temperature of the K2SO4 electrolyte in the detection tank are detected online in real-time using an integrated conductivity and temperature sensor. In this embodiment, the measured values are: electrolyte conductivity: 36.2 mS / cm (standard value 36.0 mS / cm, deviation +0.72 mS / cm, conductivity accuracy ±2%); solution temperature: 26.5℃ (standard temperature 25℃, deviation +1.5℃).
[0033] The measured voltage value V collected in step S4 is corrected for error based on the liquid junction potential and the deviation of ambient temperature, resulting in a corrected voltage value V'. This corrected voltage value V' is then used to replace the measured voltage value V in the threshold determination of step S5. The liquid junction potential correction is -0.020V, the temperature correction coefficient is -0.001V / ℃, and the corrected voltage value V' = 0.403 - 0.02 - 0.001 × 1.5 = 0.3815V, which is taken as 0.382V.
[0034] Step S5: Compare the measured voltage value V with the preset corrosion judgment threshold. If the voltage V is greater than the corrosion judgment threshold, the aluminum shell of the battery is determined to have an electrochemical corrosion leakage risk and is marked as a defective product; otherwise, it is determined to be a qualified product.
[0035] In this embodiment, the corrosion judgment threshold is set to 0.500V. The corrected voltage value V'=0.382V is compared with the judgment threshold of 0.500V: 0.382 < 0.500V, therefore the aluminum shell of the battery is determined to be normal, there is no risk of electrochemical corrosion and leakage, it is marked as a qualified product, and it is transferred to the good product collection area.
[0036] After step S5, step S6 is further comprised: a cleaning step: removing the battery from the electrolyte detection tank, and cleaning the aqueous solution remaining on the surface of the battery housing by a combination of air blowing and roller wiping. Compressed air purging can be performed sequentially through an air blowing station for 5 seconds, and wiping is performed by a water-absorbing roller at a roller wiping station, to remove the residual K₂SO₄ aqueous solution on the surface of the battery housing, and then the battery flows into the next process.
[0037] Example 2: Reference Figures 2-4 , the difference between this example and Example 1 is that a batch of 500 square aluminum-shell lithium-ion batteries that have completed K-value testing is continuously tested to verify the accuracy and stability of the detection method of the present application. Except for the differences, everything else is the same as in Example 1.
[0038] Experimental group: 500 batteries were detected using the method of Example 1 of the present application, and the criterion was that when V' > 0.500 V, the battery is determined as a defective product.
[0039] Control group: the same batch of 500 batteries was detected using the conventional edge voltage method, the edge voltage between the positive electrode and the aluminum shell was measured, and defective products were determined according to the original standard of the production line.
[0040] AVE (average value), MAX (maximum value), MIN (minimum value), R (range), sigma (standard deviation) and 3×S (three times the standard deviation) in the detection data were calculated and compared.
[0041] The detection result data are shown in Table 1 below:
[0042] It can be seen from the above data that the control group adopts the conventional edge voltage method, and the measured values have a wide distribution range (range of 187.24 mV, standard deviation of 28.24 mV), and the 3 times standard deviation range reaches 169.42 mV, which is prone to misjudgment and missed judgment. For example, under the condition of 60% SOC, the measured edge voltage of a certain battery is 1792 mV (less than the 1800 mV threshold), and it is determined as qualified according to the method of the control group. However, when the method of Example 1 of the present application is used, the measured open-circuit voltage of the battery is 851.12 mV (much greater than the 0.500 V threshold), and it is determined as a defective product, indicating that there is a risk of missed judgment. Actual production statistics show that about 50% of corrosion risk products need to be re-measured twice for confirmation by the original method.
[0043] After adopting the method of the present application, the measured values are concentrated in distribution (the range is only 1.00 mV, and the standard deviation is only 0.28 mV), the degree of data dispersion is extremely low, which can accurately distinguish corroded and non-corroded batteries, effectively eliminate the interference of factors such as difference in positive lithium intercalation amount, electrolyte concentration fluctuation and contact impedance, and significantly reduce the rate of missed judgment and misjudgment.
[0044] Verification of long-term stability of reference electrode: Standard calomel electrode potential: 241 mV; Ag / AgCl (saturated KCl) || K2SO4 (0.3 mol / L) standard electrode potential: 197 mV; initial cell voltage: 44 mV.
[0045] During four consecutive weeks of production line application, the voltage values of the galvanic cells composed of the Ag / AgCl dual salt bridge reference electrode and the standard calomel electrode were recorded periodically as follows:
[0046] The results showed that the deviation was within ±1.7mV for the first three weeks, but reached 2.2mV in the fourth week, exceeding the stringent calibration control requirement of 3mV, indicating the need for electrode maintenance or replacement. This data validates the effectiveness of the monthly calibration strategy and ensures the long-term reliability of the testing system.
[0047] Temperature compensation coefficient verification: Place the measuring device in a water bath and measure the positive electrode voltage at different temperatures. The test values are shown in the table below:
[0048] The temperature compensation coefficient of the measurement system is calculated to be approximately -0.1 mV / ℃, which is consistent with the temperature correction coefficient used in Example 1, thus verifying the accuracy of the temperature correction formula.
[0049] In summary, the electrochemical corrosion detection method for square aluminum-cased lithium-ion batteries provided in this application is significantly superior to the traditional side voltage method in terms of detection accuracy, data stability, and production line adaptability, and has good industrial application value.
[0050] The above are exemplary embodiments disclosed in this invention. However, it should be noted that various changes and modifications can be made without departing from the scope of the embodiments of this invention as defined by the claims. The functions, steps, and / or actions of the methods according to the disclosed embodiments described herein do not need to be performed in any particular order. Furthermore, although the elements disclosed in the embodiments of this invention may be described or claimed individually, they may be understood as multiple unless explicitly limited to a singular number.
[0051] It should be understood that, as used herein, the singular form "a" is intended to include the plural form as well, unless the context clearly supports an exception. It should also be understood that, as used herein, "and / or" refers to any and all possible combinations of one or more of the associatedly listed items. The embodiment numbers disclosed above are for descriptive purposes only and do not represent the superiority or inferiority of the embodiments.
[0052] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention (including the claims) is limited to these examples. Within the framework of the invention, technical features of the above embodiments or different embodiments can be combined, and many other variations of different aspects of the invention exist, which are not provided in the details for the sake of brevity. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the invention should be included within the protection scope of the invention.
Claims
1. A method for detecting electrochemical corrosion of a square aluminum-cased lithium-ion battery, characterized in that: Includes the following steps: Step S1: After completing the K-value test on the production line, keep both the positive and negative electrodes of the square aluminum-cased lithium-ion battery in an open circuit state and use it as the battery to be tested. Step S2: Construct the detection electrochemical system, using an Ag / AgCl dual salt bridge reference electrode as the reference electrode and the aluminum metal shell of the battery under test as the working electrode. Prepare a K2SO4 aqueous solution with a concentration of 0.1~0.5mol / L as the detection electrolyte; wherein, the inner salt bridge of the Ag / AgCl dual salt bridge reference electrode is filled with saturated KCl solution, and the outer salt bridge is filled with K2SO4 solution of the same system as the detection electrolyte; Step S3: Place the battery under test in the open circuit state into the detection tank containing the K2SO4 aqueous solution, and let it stand for 3 to 5 seconds to allow the potential between the battery aluminum shell and the electrolyte to stabilize. Step S4: Attach the test probe to the outer wall of the aluminum shell of the battery under test, so that the Ag / AgCl dual salt bridge reference electrode, K2SO4 detection electrolyte, and battery aluminum shell form a closed galvanic cell circuit, and collect the measured voltage value V of the galvanic cell at an environment of 25±3℃. Step S5: Compare the measured voltage value V with the preset corrosion judgment threshold. If the voltage V is greater than the corrosion judgment threshold, the aluminum shell of the battery is determined to have an electrochemical corrosion leakage risk and is marked as a defective product; otherwise, it is determined to be a qualified product.
2. The electrochemical corrosion detection method for a square aluminum-cased lithium-ion battery according to claim 1, characterized in that: The corrosion judgment threshold in step S5 is 0.500V; when the measured voltage value V > 0.500V, it is judged as a defective product, and when V ≤ 0.500V, it is judged as a qualified product.
3. The electrochemical corrosion detection method for a square aluminum-cased lithium-ion battery according to claim 1, characterized in that: Between step S4 and step S5, there is also step S41: the conductivity and solution temperature of the detection electrolyte are detected online in real time, and the measured voltage value V collected in step S4 is corrected for error compensation based on the liquid junction potential and the deviation of ambient temperature to obtain the corrected voltage value V', and the corrected voltage value V' is used to replace the measured voltage value V for the threshold determination in step S5.
4. The electrochemical corrosion detection method for a square aluminum-cased lithium-ion battery according to claim 3, characterized in that: The concentration and temperature parameters of the detection electrolyte are collected online and synchronously using an integrated conductivity and temperature sensor.
5. The electrochemical corrosion detection method for a square aluminum-cased lithium-ion battery according to claim 1, characterized in that: The test probe is made of gold-plated copper to make low-impedance contact with the outer wall of the battery's aluminum casing.
6. The electrochemical corrosion detection method for a square aluminum-cased lithium-ion battery according to claim 1, characterized in that: Before step S1, there is also step S01: routine calibration and electrolyte maintenance. Step S01 specifically includes: monthly potential calibration of the Ag / AgCl dual salt bridge reference electrode using an electrochemical workstation, with the calibration deviation controlled within 3mV. If the deviation exceeds the limit, the reference electrode is replaced. The conductivity of the detection electrolyte is monitored in real time. When the fluctuation exceeds ±0.72mS / cm, the K2SO4 detection electrolyte is prepared and replaced.
7. The electrochemical corrosion detection method for a square aluminum-cased lithium-ion battery according to claim 2, characterized in that: The industrial screening reference voltage is 3.007V, and the internal control judgment threshold is 0.500V.
8. The electrochemical corrosion detection method for a square aluminum-cased lithium-ion battery according to claim 1, characterized in that: After step S5, step S6 is also included: cleaning step: remove the battery from the test electrolyte tank and clean the residual aqueous solution on the surface of the battery casing by air blowing and roller wiping.